ANALISIS PRODUKSI ALAT GALI MUAT DAN ALAT ANGKUT DENGAN MENGGUNAKAN METODE MATCH FACTOR DAN TEORI ANTRIAN UNTUK MEMENUHI TARGET PRODUKSI BATUBARA 48.000 TON/BULAN DI GUNUNG SELAN PT PUTRA MAGA NANDITAMA BENGKULU UTARA - Muhammad Daffa Muzaffar; Tri Gamela Saldy (Departemen Teknik Pertambangan FT UNP, 2023)
Abstract. PT Putra Maga Nanditama is a coal mining company located in Gunung Selan, Bengkulu. This company uses the open pit mining method. The failure to achieve the production target of 48,000 tons/month was caused by several problems, namely the problem of tool waiting time, equipment damage, productivity of loading and unloading equipment and unstable transportation equipment.The misalignment between the loading and digging equipment and the hauling equipment results in waiting time for the equipment. Based on research conducted in August 2022, the productivity of 1 unit of Doosan DX300 Excavator was 154.79 tons/hour and 5 units of DT Hino Ranger 500 reached 111.8 tons/hour. From the results of the production analysis using the match factor method after the repair, the value of MF = 0.85 is obtained and the queuing theory after the repair is obtained by the EU on the Doosan DX300 Excavator which is 74% and the EU on the DT Hino Ranger 500 which is 75%. Then the productivity obtained after repairs from mechanical devices that work is 77,490.54 tons/month which shows that the production target at PT Putra Maga Nanditama has been achieved at 48,000 tons/month.